Ramon Llull and the ars conuertendi: Anthropology, apologetics, discussion and hermeneutics - Pardo Pastor, Jordi (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The present article analyses how the medieval writer Ramon Llull developed a hermeneutic, anthropological and theological system based on elements common to Christianity, Judaism and Islam, intended to bring the believers of the later two religions to «recognise» the Truth of Christianity and to convert to it through a process of discussion and education. A good example of this system is the Llibre del gentil e dels tres savis. On the other hand, the anthropology of Ramon Llull roots itself on two basic principles: God as creator and reality as the product of this God. Since the human being is the most perfect creature, he is able, through faith, to attain to divine knowledge (ascensus) and, therefore, assimilate himself, mutatis mutandis, to Divinity. Anthropology and Theology would join together to bring forward the apologetical task of converting the nonbeliever, making use of those dignitates dei that are indisputable for all the three monotheistic medieval religions.
Keywords: Ramon Llull; anthropology; religious discussion; education; conversion; knowledge of God; attributes of God